2004
DOI: 10.1124/jpet.103.058339
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Reduces Cardiac Injury and Expression of β1-Adrenoceptor upon Ischemic Insult in the Rat Heart

Abstract: To test the hypothesis that estrogen confers cardioprotection by suppressing the expression of ␤-adrenoceptor (␤-AR), we first correlated the infarct size in response to ischemic insult and ␤-AR stimulation with the expression of ␤ 1 -AR in sham, ovariectomized (Ovx) and estrogen replaced (Ovx ϩ E 2 ) rats. When ␤-AR is being activated during ischemia, the infarct size was significantly greater in Ovx than in the sham and Ovx ϩ E 2 rats. There is a negative correlation between the infarct size and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 33 publications
8
52
0
2
Order By: Relevance
“…It has been shown that the estrogen administration could suppress the expression of ␤-adrenoceptor in rat cardiomyocytes (Kam et al, 2004). Our results indicated that the heart vtgAo1 expression could be regulated by both E2 and adrenergic agonist treatments.…”
Section: Figsupporting
confidence: 52%
“…It has been shown that the estrogen administration could suppress the expression of ␤-adrenoceptor in rat cardiomyocytes (Kam et al, 2004). Our results indicated that the heart vtgAo1 expression could be regulated by both E2 and adrenergic agonist treatments.…”
Section: Figsupporting
confidence: 52%
“…In addition, the pattern of LV remodeling in female rats differs with a smaller increase in hypertrophy of the viable portions of the LV, but comparable LV cavity enlargement and systolic dysfunction. Despite similar infarct size, females have less abnormal LV diastolic filling compared with males (21). However, there are no reports to date of sex-related deterioration of cardiac function in post-MI mice.…”
mentioning
confidence: 89%
“…On the other hand, women are known to benefit from the cardioprotective actions of sex hormones which discontinue with the onset of menopause (21,24). Estrogen indirectly affects cardiac function by increasing elastin and decreasing collagen accumulation in blood vessels.…”
mentioning
confidence: 99%
“…Several studies demonstrate that myocardial βAR-mediated positive inotropic responses are greater in male hearts than matched female hearts, and these differences are mediated by a lower level of β1AR-signalling. The reduced myocardial β1AR-signalling in ovulating females appears protective from myocardial insults including high catecholamines from stress stimuli as well as ischaemia-reperfusion injury 29,89 . Oophrectomy removes this protective effect in preclinical models, and is associated with an increase in β1AR-signalling and inotropy.…”
Section: Post-menopausal Hormonal Status and Catecholaminergic Responsesmentioning
confidence: 99%